2016
DOI: 10.1016/j.neuron.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Linking Cholinergic Interneurons, Synaptic Plasticity, and Behavior during the Extinction of a Cocaine-Context Association

Abstract: Despite the fact that cholinergic interneurons are a key cell-type within the nucleus accumbens, a relationship between synaptic plasticity and the in vivo activity of cholinergic interneurons remains to be established. Here, we identify a three-way link between the activity of cholinergic interneurons, synaptic plasticity, and learning in mice undergoing the extinction of a cocaine-context association. We found that activity of cholinergic interneurons regulates extinction learning for a cocaine-context assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 41 publications
12
49
0
Order By: Relevance
“…Overall, these results suggest that depression of spontaneous glutamate release onto NAshell MSNs occurs during reexposure to context regardless of whether that context is associated with extinction or self-administration alone. Similar results have been described for D1-MSNs in NAcore 27 and in nucleus accumbens when mice underwent extinction of conditioned place preference 15.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Overall, these results suggest that depression of spontaneous glutamate release onto NAshell MSNs occurs during reexposure to context regardless of whether that context is associated with extinction or self-administration alone. Similar results have been described for D1-MSNs in NAcore 27 and in nucleus accumbens when mice underwent extinction of conditioned place preference 15.…”
supporting
confidence: 84%
“…Extinction decreases pre-synaptic glutamate release in nucleus accumbens. 15 The expression of calcium permeable (CP)-AMPARs in spines of NAshell MSNs contacted by infralimbic prefrontal cortex (PFC) after prolonged withdrawal oppose drug seeking. 9 Finally, NMDA glutamate receptor (NMDAR) signaling in nucleus accumbens enhances extinction learning.…”
Section: Introductionmentioning
confidence: 99%
“…Given that plasticity of PL synapses in NAc is thought to be a site of reward-related learning (Britt et al 2012; Otis et al 2017; McFarland et al 2003; Pascoli et al 2014; J. Lee et al 2016), we hypothesized that these neurons could support the formation of social-spatial associations by providing information to the NAc about the location of social encounters.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, a large number of distributed but interconnected brain areas have been implicated, including the prelimbic cortex (PL, part of the medial prefrontal cortex) and several of its projection targets (e.g. the amygdala, ventral tegmental area, NAc) (Okuyama et al 2016; Wong et al 2016; Lin et al 2011; Hitti & Siegelbaum 2014; Yizhar et al 2011; E. Lee et al 2016; van Kerkhof et al 2013; Takahashi et al 2014; Wang et al 2011; Bicks et al 2015; Gunaydin et al 2014; Felix-Ortiz et al 2016; Amadei et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is not too surprising that newer studies have revealed striatal acetylcholine to have a modulatory role rather than directly reinforcing properties. Neither optogenetic activation nor inhibition of choline acetyltransferase (ChAT)-positive neurons in the NAc is capable of inducing place preference or avoidance (Lee et al, 2016).…”
Section: Acetylcholine and Reinforcement Learningmentioning
confidence: 99%